Triplet Excitons in Highly Efficient Solar Cells Based on the Soluble Small Molecule p‐DTS(FBTTh2)2. Issue 7 (12th December 2016) - Väth, Stefan; Tvingstedt, Kristofer; Baumann, Andreas; Heiber, Michael C.; Sperlich, Andreas; Love, John A.; Nguyen, Thuc‐Quyen; Dyakonov, Vladimir
Abstract : Triplet exciton formation in neat 7, 7‐(4, 4‐ bis (2‐ethylhexyl)‐4H‐silolo[3, 2‐b:4, 5‐b′] dithiophene‐2, 6‐diyl) bis (6‐fluoro‐4‐(5′‐hexyl‐[2, 2′‐bithiophen]‐5‐yl)benzo[c][1, 2, 5]thiadiazole) (p‐DTS(FBTTh2 )2 ) and blends with [6, 6]‐Phenyl C70 butyric acid methyl ester (PC70 BM), with and without the selective solvent additive 1, 8‐diiodooctane, is investigated by means of spin sensitive photoluminescence measurements. For all three material systems, a significant amount of long living triplet excitons is detected, situated on the p‐DTS(FBTTh2 )2 molecules. The characteristic zero‐field splitting parameters for this state are identified to be D = 42 mT (1177 MHz) and E = 5 mT (140 MHz). However, no triplet excitons located on PC70 BM are detectable. Using electrically detected spin resonance, the presence of these triplet excitons is confirmed even at room temperature, highlighting that triplet excitons form during solar cell operation and influence the photocurrent and photovoltage. Surprisingly, the superior performing blend is found to have the largest triplet population. It is concluded, that the formation of triplet excitons from charge transfer states via electron back transfer has no crucial impact on device performance in p‐DTS(FBTTh2 )2 :PC70 BM based solar cells. Abstract : Various pathways of triplet exciton formation, such as intersystem crossing and electron back transfer (EBT), are investigated in the high‐performing organic photovoltaics system 7, 7‐(4, 4‐ bis (2‐ethylhexyl)‐4H‐silolo[3, 2‐b:4, 5‐b′] dithiophene‐2, 6‐diyl) bis (6‐fluoro‐4‐(5′‐hexyl‐[2, 2′‐bithiophen]‐5‐yl)benzo[c][1, 2, 5]thiadiazole):[6, 6]‐Phenyl C70 butyric acid methyl ester (PC70 BM). Using spin sensitive detection of photoluminescence and photocurrent in thin films and solar cells, it is concluded that the formation of triplet excitons via EBT does not have a crucial impact on the device efficiency.